Construction of Non Performing Loan Settlement at State Owned Bank (Bank BUMN) Post of Revocation of Authority of the State Receivable Affairs Committee (PUPN) - Agus Bambang Nugraha (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The problem of bad credit is inevitable in the banking business. Although anticipation with pre- and post-credit risk management has been carried out as well as possible, good credit performance may not necessarily be achieved. Because the operational reality of the banking industry is subject to the dynamic performance of debtors from time to time in the tenor of their debt. This paper will review how the construction of bad credit management in state-owned banks, after the decision of the Constitutional Court number 77/PUU-X1X/2011, where the extension and role of PUPN no longer exists in the structure of bad credit management at the state-owned bank. This means that the banking sector has absolute sovereignty to solve the NPL problems it faces. This research is a literature study, which will qualitatively analyze that reality with secondary sources. From the results of the study, it can be concluded that (1) State-owned banks have full sovereignty in the settlement of bad loans, (2) Banks must strengthen risk management, without compromising the achievement of sales targets, (3) Settlement of bad loans in order to prioritize a win-win solution between debtors and creditors by adhering to the principle of justice.